2022
DOI: 10.1002/gps.5686
|View full text |Cite
|
Sign up to set email alerts
|

Brain pathology and cognitive scores prior to onset of late‐life depression

Abstract: Objectives: Understanding the biological changes that occur prior to onset of latelife depression (LLD) is key to its prevention. To investigate potential predictors of LLD, we assessed cognitive scores and neurodegenerative and vascular biomarkers in healthy older adults who later developed depression. Methods: Longitudinal data from the Alzheimer's Disease Neuroimaging Initiative of 241 cognitively unimpaired and non-depressed older adults aged 56-90 at baseline with at least 4 years of follow-up were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
(168 reference statements)
1
2
0
Order By: Relevance
“…In our sample, there were several cognitive differences between LOD and EOD groups: although most of them were related to chronological age rather than to the age of onset, suggesting they could simply reflect the impact of brain ageing ( Diniz et al , 2021 ), memory dysfunction has emerged as a true feature of LOD. This finding was consistent with prior studies such as Mackin et al (2014 ), who reported a correlation between memory impairment and LOD in older adults with depression and executive dysfunction and, more recently, a study of healthy older individuals who later developed depression, among whom mild cognitive impairment preceded depression onset ( Almdahl et al , 2022 ). Another characteristic that was associated with LOD in our sample was an increased risk of developing dyskinesias, notwithstanding the assumption of lower antidepressant doses.…”
Section: Discussionsupporting
confidence: 92%
“…In our sample, there were several cognitive differences between LOD and EOD groups: although most of them were related to chronological age rather than to the age of onset, suggesting they could simply reflect the impact of brain ageing ( Diniz et al , 2021 ), memory dysfunction has emerged as a true feature of LOD. This finding was consistent with prior studies such as Mackin et al (2014 ), who reported a correlation between memory impairment and LOD in older adults with depression and executive dysfunction and, more recently, a study of healthy older individuals who later developed depression, among whom mild cognitive impairment preceded depression onset ( Almdahl et al , 2022 ). Another characteristic that was associated with LOD in our sample was an increased risk of developing dyskinesias, notwithstanding the assumption of lower antidepressant doses.…”
Section: Discussionsupporting
confidence: 92%
“…However, some studies have added nuance to this conclusion. When studying cognitively normal populations with LLD, some associations with pathological forms of Aβ have been found [104][105][106][107][108][109], while some studies still find no correlation [110][111][112]. Though interpretation of these results is challenging, one explanation could be that early AD pathological hallmarks are associated with depression-onset in some individuals because these early symptoms are actually prodromal for AD.…”
Section: Pathological Hallmarks Of Neurodegenerative Disordersmentioning
confidence: 99%
“…This group showed mild cognitive decline before depression onset. Cerebrospinal fluid (CSF) β-amyloid (Aβ) levels and white matter hyperintensities (WMH) suggested that subtle cognitive changes that occur prior to LLD may be explained by the underlying pathological aging process, disrupting brain networks involved in emotional and cognitive processing, thus disposing older adults to depression (Almdahl et al 2022 ). In older age bipolar disorder, cognitive dysfunction is more severe than in LLD, but in the same domains as in LLD, which cannot be fully explained by the severity of depressive symptoms (Orhan et al 2023 ).…”
Section: Lld and Cognitive Impairmentmentioning
confidence: 99%
“…A longitudinal study of older adults showed that baseline cortical Aβ burden, CSF amyloid levels and WMH were significant predictors of incipient depression. Compared to the non-depressed group, hippocampal volume was not reduced before onset, but was reduced following depression (Almdahl et al 2022 ). Conversely, two other studies showed that LLD was associated with reduced cortical Aβ burden.…”
Section: Pathogenic Factors In Lldmentioning
confidence: 99%